THE INFLUENCE OF AGE FACTORS AND THE LEVEL OF LANGUAGE COMPETENCE ON THE PROCESS OF LEARNING FOREIGN LANGUAGES - Akramova Mohinur Akramovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
This article examines the role of age and language proficiency in foreign language teaching. It demonstrates that a differentiated approach based on students’ age and level improves language acquisition and learning motivation. The findings support the advisability of adapting teaching methods and content to foster sustainable communicative competence.